OBESITY, BARIATRIC SURGERY, AND RHEUMATOLOGIC DISEASES: THE IMPACT OF METABOLIC SURGERY ON SYSTEMIC INFLAMMATION - Elboboyeva Saida Gulom qizi; Ibragimova Jasmina Bakhodir qizi (Bright Mind Publishing, 2026)
Obesity has emerged as one of the most significant global health challenges of the twenty-first century, with profound metabolic, cardiovascular, and immunological consequences. Beyond its well-established association with type 2 diabetes mellitus, hypertension, and cardiovascular disease, obesity is now increasingly recognized as a state of chronic low-grade systemic inflammation. This inflammatory milieu plays a critical role in the pathogenesis and progression of multiple immune-mediated and degenerative disorders, including a broad spectrum of rheumatologic diseases.
Keywords: multiple immune-mediated and degenerative disorders, including a broad spectrum of rheumatologic diseases